2003
DOI: 10.3171/jns.2003.98.2.0319
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic vasospasm and outcomes following aneurysmal subarachnoid hemorrhage: a comparison between surgical repair and endovascular coil occlusion

Abstract: Patients with better clinical grades (WFNS Grades I-III) at hospital admission were less likely to suffer symptomatic vasospasm when treated by endovascular coil occlusion, compared with craniotomy and clip application. Nevertheless, there was no significant difference in overall outcome at the longest follow-up examination between the two treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(73 citation statements)
references
References 28 publications
3
65
1
4
Order By: Relevance
“…[1][2][3][4] The current strategies for preventing vasospasm comprise the systemic administration of the calcium channel blocker nimodipine. [5][6][7] Moreover, the use of intracisternal thrombolysis 8 and the intracisternal application of nicardipine-prolonged implants 9,10 demonstrated effectiveness in preventing cerebral vasospasm.…”
mentioning
confidence: 99%
“…[1][2][3][4] The current strategies for preventing vasospasm comprise the systemic administration of the calcium channel blocker nimodipine. [5][6][7] Moreover, the use of intracisternal thrombolysis 8 and the intracisternal application of nicardipine-prolonged implants 9,10 demonstrated effectiveness in preventing cerebral vasospasm.…”
mentioning
confidence: 99%
“…Only 51% of the patients suffering angiographic CVS presented with TCD criteria for CVS. In a consecutive series of 415 patients, Rabinstein et al [10] observed an incidence of symptomatic CVS in 39% in patients who underwent clipping compared to 30% in patients who underwent coiling. The authors demonstrated that patients with better clinical grades (WFNS I-III) at hospital admission were less to suffer symptomatic CVS when treated with endovascular techniques compared with surgical treatment.…”
Section: Incidence Of Vasospasm and Risk Factorsmentioning
confidence: 99%
“…Moreover, differences in outcome between patients undergoing endovascular and surgical treatment have not been extensively studied [5][6][7][8][9][10][11][12]. In terms of comparison of quality of life between patients treated with endovascular and surgical techniques, only one study has been published so far [13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited success achieved by these approaches, 26-38% patients either develop sequelae or die of severe symptomatic vasospasm [12][13] . The success of the current treatment strategies against delayed cerebral vasospasm after SAH remain inconsistent, and seem to have variable effects on the outcome 14 . Despite its clinical significance and the extensive research efforts placed into elucidating its pathogenesis and therapy, vasospasm remains as an incompletely understood and important clinical problem.…”
Section: Introductionmentioning
confidence: 99%